THE ABILITY OF FRESHMEN IN DEVELOPING DESCRIPTIVE PARAGRAPH - Naja, Emmi (Jurnal Bahasa Lingua Scientia, 2012)
This study concerns on students? ability in developing a descriptive paragraph based on three paragraph components and characteristics of good paragraph, but it is not based on the grammatical error.  It focuses on descriptive paragraph because it is supposed as one type of paragraph that will be use more by students both during their courses and their works. The populations of this study are students first semester of English department in STAIN Tulungagung. There are 31 students (20%) as samples selected randomly, and they are taken from 152 students who divided into 5 classes. They are assigned to develop descriptive paragraph in the end of the semester as their final project.  The result of this study shows that generally students? ability in developing descriptive paragraphs are good, it is shown from their average score (72.14).  Moreover, there are 22 or 71% students who get 75 up to 84, means that most of their ability in developing good descriptive paragraphs are very good.